2013
DOI: 10.1139/cjfr-2012-0298
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of forest ownership type and location on roundwood utilization at the stump and top in a region with small-diameter markets

Abstract: Research conducted in a variety of hardwood regions across the United States has indicated that utilization of small-diameter roundwood is hindered by a lack of markets. Efficient removal of such material could enable silvicultural practices to improve stand conditions and economic return for landowners. However, evidence from other studies has suggested that markets alone may not be enough to encourage small-diameter utilization, and that management decisions are important as well. This study sought to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, low-grade hardwoods have long been used in the manufacture of pulp and paper. Recent studies have shown, for example, that the presence of pulpwood markets is an important component to small-diameter harvesting (Bumgardner et al 2013). Recently, research also has focused on modelling the economic and resource feasibility of using small trees and logging residue in biomass and bioenergy systems (Wu et al 2011, Thiel et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low-grade hardwoods have long been used in the manufacture of pulp and paper. Recent studies have shown, for example, that the presence of pulpwood markets is an important component to small-diameter harvesting (Bumgardner et al 2013). Recently, research also has focused on modelling the economic and resource feasibility of using small trees and logging residue in biomass and bioenergy systems (Wu et al 2011, Thiel et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…I nterest in the use of small-diameter roundwood and forest-derived biomass for energy has increased dramatically in the United States over the last several decades (Boyce 1979, Skog and Rosen 1997, LeVan-Green and Livingston 2001, Galik et al 2009, Bumgardner et al 2013. Forest harvest residues, in particular, have been targeted as a potential carbon-friendly alternative to fossil fuels used in energy production (Repo et al 2010, Domke et al 2012, Goerndt et al 2012.…”
mentioning
confidence: 99%